CONTRAINTES SOCIO-ECONOMIQUES ET ANALYSE SWOT DE LA PROMOTION DE L’ARBRE DANS LES VILLES DU CENTRE-BENIN (AFRIQUE DE L’OUEST) /Promotion of tree in the compounds of Central-Benin cities (West Africa): an assessment of its assets and constraints - ZOHOUN, Elisée Prucelle; AZALOU-TINGBE, Emillia; ZAKARI, Soufouyane; YABI., Ibouraïma. (My University, 2023)
Nature-based solutions hold promise for cities, given their development challenges and vulnerability to climate change. This research is based on the fact that knowledge of public perceptions of trees is necessary for planning tree conservation and planting initiatives in rapidly changing landscapes. This article aims to identify the assets and constraints related to the promotion of trees in the compounds of the cities of Central Benin (cities of Parakou, Dassa-Zoumè and Savalou) based on the perceptions of urban residents. Samples of 370, 365 and 360 inhabitants respectively in Parakou, Dassa-Zoumè and Savalou are used to collect information. A SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis was performed on the responses obtained to identify assets (strengths and opportunities) and constraints (weaknesses and threats). The decision of the landowner, the lack of place, the lack of technicality, the socio-economic problems constitute the main constraints of the promotion of the tree in the cities of Centre-Benin. To meet the challenge, these cities have assets such as the majority proportion of landowners, the high level of education, the presence of several socio-cultural groups, the climate and favorable soils, the presence of nurserymen and the availability of seedlings, the national tree day.
Keywords: nature-based solutions; city dweller; perception; sustainable cities; tree planting; urban forest